When the Cough Does Not Improve: A Review on Protracted Bacterial Bronchitis in Children - Gallucci, Marcella; Pedretti, Melissa; Giannetti, Arianna; di Palmo, Emanuela; Bertelli, Luca; Pession, Andrea; Ricci, Giampaolo (Frontiers in Pediatrics, 2020)
Chronic cough is defined as a daily cough that persist longer than 4 weeks. Protracted Bacterial Bronchitis (PBB) is a common cause of chronic wet cough in pre-school children with no symptoms or signs of other specific causes and resolution usually follows a 2 weeks course of an appropriate oral antibiotic. The diagnosis is mainly clinical, generally no instrumental examinations are necessary. The most common bacteria found in the Bronchoalveolar lavage (BAL) of subjects with PBB include H. influenzae, S. pneumoniae and M. catarrhalis. Nowadays there is no certain evidence of the role of viruses in PBB pathogenesis even though different types of viruses have been detected in BAL from children with PBB. Airway malacia is commonly found in children with PBB, conversely there is no correlation with any type of immunodeficiency. Amoxicillin-clavulanate acid is the most commonly used antibiotic as first line, prolonged therapy (longer than 2 weeks) is sometimes required to cough resolution. When the wet cough does not improve despite prolonged antibiotic treatment, an underlying disease should be considered. Moreover, there are several hypotheses of a link between PBB and bronchiectasis as recent evidences show that recurrent PBB (> 3 ep/years) and the presence of H. influenzae infection in the lower airways seem to be significant risk factors to develop bronchiectasis. This underlines the need to monitor children with PBB over time and to consider chest computerized tomography (CT) imaging in those with risk factors for bronchiectasis. In this brief review we summarise the main clinical and pathogenetic findings of PBB, a disease that may be related to a relevant morbidity and decreased quality of life during the pediatric age.